PENGARUH PUPUK KANDANG SAPI DAN PEMANGKASAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI KERITING DI TANAH GAMBUT - Syarifatul Awaliyah; Saijo Saijo; Djoko Eko Hadi Susilo (Universitas Lambung Mangkurat, 2026)
The objective of this study was to analyze and examine the effects of cattle manure, pruning, and their interaction on the growth and yield of curly chili plants on peat soil. The experimental design used was a factorial Completely Randomized Design (CRD) with two treatment factors and four replications. The first treatment factor was cattle manure: K1 = 20 t ha⁻¹, K2 = 30 t ha⁻¹, and K3 = 40 t ha⁻¹. The second treatment factor was pruning: P0 = no pruning, P1 = apical pruning, and P2 = water shoot pruning. Data were analyzed using the F-test at significance levels of α = 0.05 and 0.01. Mean differences among treatments were tested using the HSD (Honestly Significant Difference) test at the 0.05 significance level.The results showed that the interaction between the two treatment factors had no significant effect. The cattle manure treatment significantly affected the fruit diameter of curly chili, with the most efficient dose being 20 t ha⁻¹. The pruning treatment significantly affected fruit length and fruit weight, with water shoot pruning being the most effective technique.